2022
DOI: 10.1002/adma.202203580
|View full text |Cite
|
Sign up to set email alerts
|

Room‐Temperature Anode‐Less All‐Solid‐State Batteries via the Conversion Reaction of Metal Fluorides

Abstract: All‐solid‐state batteries (ASSBs) that employ anode‐less electrodes have drawn attention from across the battery community because they offer competitive energy densities and a markedly improved cycle life. Nevertheless, the composite matrices of anode‐less electrodes impose a substantial barrier for lithium‐ion diffusion and inhibit operation at room temperature. To overcome this drawback, here, the conversion reaction of metal fluorides is exploited because metallic nanodomains formed during this reaction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 62 publications
0
33
0
Order By: Relevance
“…Based on single-crystal XRD studies conducted on multiple samples for each composition to ensure reproducibility, we find that Li 4+x P 1−x Si x S 4 I�where x = 0.12 and 0.30�adopts a structure with a primitive tetragonal unit cell with space group P4/nmm, No. 129, Z = 2 (x= 0.12, refined lattice parameters: a = b = 8.4813(6) Å, c = 5.927 (4) Å, and V = 426.34 (7); x= 0.30, a = b = 8.5090(7) Å, c = 5.9473(5) Å, and V = 430.6(1) Å 3 ). Table 1 displays the structural data for x = 0.30, while Tables S1−S6 in the Supporting Information list that data for x = 0.12 (Table S2) along with other crystallographic information for both compositions such as bond distances and anisotropic displacement parameters.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on single-crystal XRD studies conducted on multiple samples for each composition to ensure reproducibility, we find that Li 4+x P 1−x Si x S 4 I�where x = 0.12 and 0.30�adopts a structure with a primitive tetragonal unit cell with space group P4/nmm, No. 129, Z = 2 (x= 0.12, refined lattice parameters: a = b = 8.4813(6) Å, c = 5.927 (4) Å, and V = 426.34 (7); x= 0.30, a = b = 8.5090(7) Å, c = 5.9473(5) Å, and V = 430.6(1) Å 3 ). Table 1 displays the structural data for x = 0.30, while Tables S1−S6 in the Supporting Information list that data for x = 0.12 (Table S2) along with other crystallographic information for both compositions such as bond distances and anisotropic displacement parameters.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…All-solid-state batteries (ASSBs) are considered to be a next generation energy storage technology that promises low cost, high performance, and superior safety. Currently employed organic liquid electrolytes show some disadvantages including high flammability and risk of leakage. , Their replacement with safer, more reliable solid electrolytes (SEs) has the potential to simplify battery design, alleviate safety concerns, and provide superior energy density by the implementation of a lithium–metal anode or anode-less designs. Solid electrolytes with high ionic conductivities at room temperature (RT) (∼10 –3 – 10 –2 S·cm –1 ) play a crucial role in the development of ASSBs. Over the decades, significant progress has been achieved in ASSBs with new SEs that also optimize electrical and mechanical properties. Among the possible inorganic SSEs, sulfide-based materials are particularly promising, as they can show a unique combination of characteristics critical to the design of crystalline superionic conductors. These include ionic conductivities comparable to, or even beyond, those of liquid electrolytes owing to an often-high concentration of mobile ions and low elastic modulus on the order of 20–40 GPa that contribute to form a close physical contact with the electrode materials, thereby improving cycling performance in ASSBs. , The higher polarizability of sulfide-based electrolytes compared to oxide SEs softens the interaction between the Li + mobile ions and the anion framework, typically enhancing the mobility of the mobile species, leading to high ionic conductivities (10 –3 to 10 –2 S·cm –1 ) .…”
mentioning
confidence: 99%
“…At the same time, they regulated the internal voids in terms of size by packing the nickel particles with controlled sizes and distributions, which led the authors to learn that the smaller voids result in more uniform penetration of Li metal via the coble creep mechanism. This nickel-based electrode was able to operate successfully even at 30 • C. Furthermore, Lee et al demonstrated stable cycling of SSE-based ALASSBs even at room temperature (RT) using the conversion reaction of silver fluoride (AgF) [38]. During Li plating, the phase of the active material becomes separated into silver-lithium (Ag-Li) alloy and lithium fluoride (LiF).…”
Section: Sulfide Solid Electrolytes (Sses)mentioning
confidence: 99%
“…Consequently, the energy density of a 0.6 Ah pouch cell exceeded 900 Wh L À 1 and the cell maintained 89 % of the initial discharge capacity over 1000 times cycles. Recently, through the in situ reaction of metal fluoride (MF x ) with Li metal, Lee et al [160] fabricated an anode-free interface composed of Li metal alloy (LiÀ M) and Li fluoride (LiF), where the electronically insulating LiF could suppress the Li dendrites, and the LiÀ M alloy acted as a nucleation seed to promote uniform Li plating. As shown in Figure 15b, among various metal fluorides (MFx, M = Ag, Sn (II), In, Zn, Al, Sn (IV)), AgF showed the nucleation overpotential of 0.92 mV in the alloying reaction.…”
Section: Anode-free Anodesmentioning
confidence: 99%
“…Copyright 2020, Springer Nature. b) Galvaanostatic voltage profiles of Li plating on the electrodes containing AgF, SnF 2 , InF 3 , ZnF 2 , AlF 3 , and SnF 4 [160]. Copyright 2022, Wiley-VCH.…”
mentioning
confidence: 99%